MODEL PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI: ANALISIS ADDIE, 4D, DAN ASSURE - Asti Cahya Dewi; Fitria Salsabiila; Rasikha Auliya Arifin; Rafi Nur Aqshal; Hesti Kusumaningrum (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
The rapid development of information and communication technology has encouraged the integration of digital-based media into educational practices to improve learning effectiveness and student engagement. This study aims to analyze three widely used instructional development models ADDIE, 4D, and ASSURE in the context of technology-based learning media development. Using a literature review method, this research examined relevant books, journal articles, and academic publications to describe the characteristics, stages, and applicability of each model. The findings show that the ADDIE model provides a systematic and continuous framework for designing instructional products; the 4D model emphasizes structured product development up to dissemination; while the ASSURE model focuses on integrating media and technology based on learner characteristics and active participation. Each model offers distinct strengths: ADDIE is adaptable and comprehensive, 4D is practical for structured product development, and ASSURE is effective for classroom-based technology integration. In conclusion, the three models can serve as valuable references for educators in selecting appropriate development frameworks according to instructional needs and learning objectives in technology-based environments.